(untitled) (Olhar de Professor, 2023)
The present essay explores the different roles and forms taken on by education in the latest centuries, with emphasis on its school and non-school conformation and the existence of different educational practices which permeate the set of organizations and private apparatuses of hegemony. In this scenario, the role of educationists in these spaces of non-school education is defended, given the necessity to imprint a proper pedagogical approach to the practices developed in these locations. In order to contribute to the building of such curricular and methodological devices aimed at the training and qualification of educationists and the investigation of their practices in non-school contexts, a theoretical-investigative matrix composed of political-pedagogical areas of action and theoretical-pedagogical fields is proposed. This mold blends and organizes the theoretical-normative, the ethical-political and the didactic-pedagogical foundations specific to the proposed scopes and fields.